การวิเคราะห์หนังสือชีวประวัติของคนไทยที่จัดพิมพ์ระหว่าง พ.ศ.2524-2543 - จันทร์เพ็ญ ฉันทอภิชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research is to analysis Thai biographies published from 1981 to 2000 in terms of the producers, the authors, the contents, the styles of presentation and their compositions. 770 biographies are recorded on the recording forms. The research results reveal that most of the biographies are biography type, are published by private publishers, are wrtitten by 223 authors, contain biographies of those who are alive. teh styles of presentation are mostly narrative. Most of the biography contents are concerning their work, the accomplishment, the education and the birth information. The majority of other subjects area covered in biographies is the social sciences. The illustrations contained are mostly photography.